Teodozja odchodzi - Piechowski, Jerzy (Lodz : Wydawn. Lodzkie, 1989)
An historical novel of the 13th century Poland, at the time of the 4th Crusade.
Keywords: Crusades -- Fourth, 1202-1204 -- Fiction; Poland -- History -- 13th century -- Fiction